TASK-BASED INSTRUCTION AND ITS IMPACT ON WRITING PROFICIENCY - Abdurasulova Maftuna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article examines the impact of Task-Based Instruction (TBI) on writing proficiency. TBI, a pedagogical approach centered around the use of meaningful tasks to facilitate language learning, has gained significant traction in recent years. This study investigates how TBI influences the writing skills of learners, focusing on both linguistic accuracy and fluency. Through a combination of qualitative and quantitative methods, including classroom observations, student interviews, and writing assessments, this research provides insights into the effectiveness of TBI in enhancing writing proficiency. The findings suggest that TBI can lead to substantial improvements in students' writing abilities, particularly in terms of content organization, vocabulary use, and grammatical accuracy.